The Effectiveness of the Jones/Davis Type By-Catch Reduction Device (BRD) to Reduce Unintended Catch of Trawl Fisheries - Andhika Prima Prasetyo; Rudy M. Purwoko; Hendri Antoro (Aceh Journal of Animal Science, 2017)
Reduction by-catch of commercial fishing are become major concern, especially prawn trawl fisheries. By-catch reduction device developed to address that issue. However, there were trade-off problems regarding the implementation the BRD in trawl fisheries that is the effectiveness of the BRD. The performance of BRD was questionable on the effectiveness in term of reduction the by-catch and maintenance amount of target catch. This essay examines the performance of Jones-Davis type BRD to reduce by-catch and its impact to prawn catch in Cleveland Bay. An experimental fishing has been conducted (control-net and BRD-net; Pair-trawl method) to assess the effectiveness of by-catch reduction which examined with Wilcoxon Rank Test. The result shows that trawl equipped by BRD significantly reduce by-catch by 22.2% (Z = -4.6406, p-value = 0.0001) and retained prawn catch which was no significant difference inprawn catch between BRD and control nets (Z = -1.9218, p-value = 0.0546). Therefore, that evidence could be argued to convince about the BRD benefits to commercial prawn trawl fisheries.